Mulberroside A Accumulation in Mulberry Plantlets from In Vitro Culture and Hydroponic System - Natvara Damrongmongcolkul; Saranya Phunpruch; Pana Lohasupthawee (Current Applied Science and Technology, 2022)
In this study, nodal explants cultured in MS medium supplemented with BAP 4mg/l and NAA 0.5 mg/l induced 3.33 shoots per explant within 4 weeks. The elongated multiple shoots were transferred to rooting media. The best root development was found on MS medium without PGRs within 10 days. The acclimatized plants were transferred to a deep-water hydroponic system with different concentrations of MS nutrient solution without sucrose addition. The results showed that mulberry plants cultivated in 1/8 MS nutrient solution gave the highest growth index. For mulberroside A determination, the results showed that mulberroside A accumulation in roots were higher than in shoots of mulberry plants both for in vitro culture and in the hydroponic system. In the case of in vitro culture, mulberroside A accumulation in roots was 20.61 mg/g DW, and in shoots was 11.98 mg/g DW. In hydroponic system, mulberroside A accumulation in roots was 17.58 mg/g DW, and in shoots was 2.34 mg/g DW. We also found that the higher concentration of MS nutrient solution, the more mulberroside A accumulation in roots of mulberry plants cultivated in the hydroponic system.
Keywords: Plant tissue culture and regeneration; Ecology and Conservation Studies; Plant Disease Management Techniques